Coronavirus outbreak in Nigeria: Burden and socio-medical response during the first 100 days - Amzat, Jimoh; Aminu, Kafayat; Kolo, Victor I.; Akinyele, Ayodele A.; Ogundairo, Janet A.; Danjibo, Maryann C. (International journal of infectious diseases, 2020)
•This paper assesses the early socio-medical response to COVID-19 in Nigeria, with a focus on the first 100 days after the index case.•The incidence of COVID-19 grows steadily in Nigeria, moving from an imported case and elitist pattern to community transmission, spreading across the states of the federation.•The paper presents a concise response framework to highlight the various multisectoral responses to the pandemic.•The response is not without some challenges, including inadequate testing laboratories, under-testing, inadequate palliatives and economic stimuli.•The potential of an overwhelming COVID-19 upsurge is still imminent in Nigeria as the country is attempting to hurriedly open the economy.•A most important lesson is the impossibility of the usual medical tourism among Nigerian elites. The coronavirus disease of 2019 (COVID-19) pandemic shocked the world, overwhelming the health systems of even high-income countries. Predictably, the situation has elicited social and medical responses from the public and governments, respectively. Nigeria recorded an imported case from Italy on February 27, 2020. Hence, this paper assesses the early socio-medical response to COVID-19 in Nigeria in the first 100 days after the index case. The paper employs analytical methods and collates data from various media reports and official sources. The incidence of COVID-19 grew steadily in Nigeria, moving from an imported case and elitist pattern to community transmission. The case fatality stood at 2.8%. The country recorded an upsurge (52% of total cases) in the transmission of COVID-19 during the short period the lockdown was relaxed. This paper presents a concise response framework to highlight some specific multisectoral responses to the pandemic. A combination of social and medical responses to a large extent helped Nigeria curtail the spread of the virus. The potential of overwhelming COVID-19 is still imminent in Nigeria as the country is attempting to hurriedly open the economy, which could sacrifice public health gains for temporary economic gains.